Chemical Investigation on the Leaves of Hibiscus Furcatus - Bindu, T.K.; Saidutty, A.; Z. Alkhathlan, Hamad; Shafi, P.M. (Asian Journal of Chemistry, 2010)
The petroleum ether (60º-80ºC) extract of the leaves of Hibiscus furcatus yielded five components. They were identified to be friedelin, β-sitosterol, taraxerol, a mixture of n-alkanes in the C30–C34 range and a mixture of n-alkanols in the C28–C34 range by chemical and physical methods.